A review on superplastic forming of Ti-6Al-4V and other titanium alloys. (March 2023) - Akula, Sai Pratyush; Ojha, Mihir; Rao, Kolla Lakshman; Gupta, Amit Kumar
Abstract: The paper presents a comprehensive review on the superplastic forming of titanium alloys, a novel forming process to manufacture components with complex geometries. This work elucidates on the dependency of superplastic forming on the initial microstructure of the alloy. An insight has been provided into microstructure refining techniques alongside the microstructure deformation-accommodation mechanisms. These microstructural studies are accompanied by potential die setups and possible process parameters for the optimal results in the final strain values. Finally, the paper discusses about the crucial applications of superplastic forming of titanium alloys and scope for further research areas in this field. Graphical Abstract: ga1